The Influence of LCD Media through PjBL-STEM on Critical Thinking Skills - Widiyono, Aan; Ghufron, Anik (JTP - Jurnal Teknologi Pendidikan, 2024)
This study investigates the impact of LCD media integrated with Project-Based Learning STEM (PjBL-STEM) on enhancing elementary school science students' critical thinking skills. Despite employing a quantitative approach and true experimental design, further clarification on the practical implementation of PjBL-STEM and the role of LCD media in the learning process would be beneficial. PjBL-STEM engages students in hands-on science projects that promote problem-solving, which is typically essential in elementary-level science curricula. However, "LCD media" lacks specificity, raising questions about whether it encompasses slides, videos, or interactive digital content. Conducted at SDN Wonosalam in Demak Regency, the research targets Grade V students using a saturated sample technique. Pretests and posttests on animal life cycle content were analyzed using the t-test to evaluate the impact of LCD-enhanced PjBL-STEM on critical thinking. Results reveal a significant positive influence, with a 2-tailed significance score of 0.005 (<0.05). Critical thinking indicators reflected high percentages: clarification (83%), assessment (81%), inference (82%), and strategies (85%). Average scores improved from a pretest mean of 68.33 to a posttest mean of 82.67, signifying growth in 21st-century skills, particularly critical thinking. This suggests that LCD-supported PjBL-STEM enhances reasoning and fosters deeper scientific understanding among elementary students.